A composite membrane material for air filtration and preparation method thereof
By using modified nonwoven fabric as the base layer and nanofiber membrane prepared by continuous electrospinning as the filter layer in the air filter material, the air filter composite membrane material is formed, and the problems of air filtration efficiency and material degradation in the prior art are solved, and the effects of efficient filtration and complete degradation are achieved.
Patent Information
- Application Number
- CN202210678507.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-06-15
AI Technical Summary
Existing air filter materials are difficult to efficiently intercept submicron-scale particulate matter, and are difficult to degrade and recycle after being discarded.
A biodegradable nonwoven fabric modified with an ammonia hydrocarbon-based silane coupling agent was used as the substrate layer, and a polyamide polymer nanofiber membrane was prepared as the filter layer by continuous electrospinning technology to form an air-filter composite membrane material.
The 100% filtration efficiency of PM2.5 particles and 99% filtration efficiency of PM0.3 particles are achieved, and the material is almost completely degraded, solving the problem of environmental pollution after waste.
Smart Images

Figure SMS_1 
Figure HDA0003695553730000011 
Figure HDA0003695553730000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of air filter materials, and in particular relates to an air filter composite membrane material and a preparation method thereof. Background Art
[0002] The problem of air pollution is getting worse day by day. Long-term inhalation of submicron particles (PM) in the air may induce a series of health problems such as respiratory infections, cardiovascular diseases, chronic lung diseases and even cancer. These fine particles are carriers of pathogenic microorganisms such as bacteria and viruses and gaseous pollutants. As an important material for resisting air pollution and protecting human health, air filter membranes have become a focus of people's reliance and general attention. Air filter materials based on polypropylene (PP) have the major problem of polluting the environment after disposal and being difficult to recycle. The development of multifunctional degradable materials is imperative.
[0003] Traditional air filter materials can no longer meet the performance requirements for high filtration efficiency of submicron particles. Electrospinning technology can prepare ultrafine fibers with diameters ranging from nanometers to micrometers, which can achieve high-efficiency and low-resistance filtration requirements. Nanofibers have the advantages of light weight, large specific surface area, and high porosity, and have attracted widespread attention in the field of fiber filter materials. CN113797649A discloses an antibacterial and antiviral air filter material and a preparation method, CN111116974A discloses a nylon nanofiber aerogel material for air filtration and a preparation method, and CN110711430A discloses a composite filter material and a preparation technology, etc., which use electrospinning technology to prepare nanofibers, but none of them involve continuous material modification and electrospinning preparation technology. The composite filter material disclosed in CN110711430A and the piezoelectric antibacterial nano-thin film air filter membrane disclosed in CN110354648A both deposit the fiber filter layer on the substrate layer without chemically bonding with the substrate. During use, especially under high air flow conditions, the nano-fiber membrane of the filter layer is easy to fall off.
[0004] At present, there is a problem that the air filter material is difficult to handle after use. For example, the degradable nanofiber membrane air filter material disclosed in CN113181711A mainly studies the degradable nanofiber layer, with ordinary non-woven fabric as the substrate. The degradable bio-based air filter material disclosed in CN105597575A uses soybean protein and polyvinyl alcohol as raw materials to prepare electrospun nanofiber membrane materials, with polyethylene screen as the substrate, and receives the nanofiber membrane layer. The substrate layer is an important supporting material for air filter membrane materials, accounting for a large proportion, polluting the environment after being discarded, and difficult to recycle. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an air filtration composite membrane material and a preparation method thereof in view of the deficiencies of the above-mentioned prior art. The air filtration composite membrane material can efficiently intercept PM 0.3 Tiny aerosol particles that can be completely degraded after disposal.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] An air filtration composite membrane material comprises a substrate layer and a filter layer, wherein the substrate layer is a carboxyl-containing biodegradable nonwoven fabric modified by an amino-hydrocarbon-based silane coupling agent; and the filter layer is a polyamide polymer nanofiber membrane prepared by continuous electrostatic spinning.
[0008] According to the above scheme, the air filtration composite membrane material according to claim 1 is characterized in that the thickness of the substrate layer is 0.08-0.2 mm, the thickness of the filter layer is 0.001-0.010 mm, the diameter of the nanofibers in the filter layer is 20-500 nm; the BET specific surface area of the air filtration composite membrane material as a whole is 0.5-20 m 2 / g, porosity 60% to 90%.
[0009] According to the above scheme, the substrate layer accounts for more than 95wt.%, and the filter layer accounts for less than 5wt.%.
[0010] According to the above scheme, the material of the nonwoven fabric is a degradable polymer material and contains carboxyl functional groups; wherein the degradable polymer includes but is not limited to polylactic acid, polyglycolic acid, amino acid polymers and the like.
[0011] According to the above scheme, the polyamide polymers include polyamide 6, polyamide 610, polyamide 66, polyamide 11, polyamide 12, polyamide 1010, polyamide 56, polyamide 4, polyamide 8, polyamide 9 and polyamide 810, etc.
[0012] According to the above scheme, the amino hydrocarbon-based silane coupling agent includes γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-(β-aminoethyl)aminopropyltrimethoxysilane, γ-ureapropyltriethoxysilane, anilinemethyltrimethylsilane, anilinemethyltriethylsilane, etc.
[0013] The present invention also provides a method for preparing the above-mentioned air filtration composite membrane material, comprising the following steps:
[0014] (1) using water and ethanol as a mixed solvent to prepare an amino-hydrocarbon-based silane coupling agent solution with a concentration of 1 to 20 wt.%; placing the nonwoven fabric on a feed reel of a continuous electrospinning machine, starting an air pump to spray the amino-hydrocarbon-based silane coupling agent solution, and then drying at a temperature of 35 to 55° C., and winding to obtain a modified nonwoven fabric substrate;
[0015] (2) The modified nonwoven fabric substrate obtained in step (1) is mounted on a feed reel of an electrospinning machine, and formic acid, acetic acid or a formic acid / acetic acid mixed solvent is used as a solvent to dissolve a polyamide polymer, and a spinning solution of 10 to 15 wt.% is prepared for continuous spinning to obtain a polyamide polymer nanofiber membrane combined with the modified nonwoven fabric substrate, i.e., an air filtration composite membrane material.
[0016] According to the above scheme, in step (1), the mixed solvent is composed of deionized water and anhydrous ethanol in a volume ratio of 1:20 to 1:5.
[0017] According to the above scheme, in step (1), the spraying amount is 0.1-10 mL / cm 2 , spraying times 1 to 10 times.
[0018] According to the above scheme, in step (2), the process parameters of continuous electrospinning are: the spinning chamber temperature is 20-60°C, the humidity is controlled at ≤50%, the nozzle is a needleless type, the spinning speed is 1-350mm / s, the voltage is set at 10-100kV, and the winding speed is controlled at 0.1-2m / min.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] First, the filter layer of the air filtration composite membrane material is a nanofiber membrane, which is light in weight, has good permeability, and a large specific surface area. It has a nanofiber structure and can efficiently intercept tiny aerosol particles and PM 2.5 The particle filtration efficiency can reach 100%, and the PM 0.3 The particle filtration efficiency can reach 99%; moreover, the substrate layer is made of a non-woven fabric that can be degraded by bio-enzymes, combined with a filter layer that can be degraded by ultraviolet light, which can ultimately achieve almost complete degradation of the air filtration composite membrane material.
[0021] Secondly, the present invention uses an amino hydrocarbon-based silane coupling agent to modify the substrate, and enhances the bonding force between the substrate and the filter layer through chemical bonding, thereby effectively improving the problem of the nanofiber membrane being easily detached during use.
[0022] Third, the method for preparing the air filtration composite membrane material of the present invention can adopt a continuous electrospinning process, which greatly improves the production efficiency. The prepared air filtration composite membrane material can be used in the fields of masks, protective clothing, indoor air purification, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM image of the nanofibers in the filtration layer of the air filtration composite membrane material obtained in Example 1.
[0024] Figure 2 This is a curve diagram of the filtration performance and pressure drop of the air filtration composite membrane material obtained in Example 1 along with the spinning time.
[0025] Figure 3 The SEM image (left) and the EDS image (right) containing silicon element of the modified substrate nonwoven fabric obtained in Example 2 are shown.
[0026] Figure 4 This is the degradation diagram of the air filtration composite membrane material obtained in Example 3. DETAILED DESCRIPTION
[0027] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0028] Example 1
[0029] An air filtration composite membrane material, comprising a substrate layer and a filter layer, wherein the substrate layer is a polylactic acid nonwoven fabric modified by γ-aminopropyltrimethoxysilane; the filter layer is a polyamide 6 nanofiber membrane prepared by continuous electrospinning. The thickness of the substrate layer is 0.0930 mm, the average diameter is 5 μm, the thickness of the modified substrate layer is 0.0960 mm, and after combining with the filter layer, the total thickness is 0.0966 mm, and the average diameter of the nanofibers in the filter layer is 50 nm. The porosity of the overall composite membrane material is about 70%, and the BET specific surface area is 19.7 m 2 / g, the substrate layer accounts for 97.5wt.%, and the filter layer accounts for 2.5wt.%.
[0030] The preparation method of the above-mentioned air filtration composite membrane material comprises the following specific steps:
[0031] (1) Deionized water and anhydrous ethanol in a volume ratio of 1:9 are prepared into a mixed solvent, and γ-aminopropyltrimethoxysilane as a silane coupling agent is selected to prepare a solution with a concentration of 10 wt.%; a polylactic acid (PLA) non-woven fabric roll with a width of 1 m and a thickness of 0.0930 mm is placed on a feed reel of a continuous electrospinning machine, and the prepared silane coupling agent solution is poured into a spray gun, and an air pump is started to spray the PLA non-woven fabric, and the spraying amount each time is controlled to be 1 mL / cm 2, sprayed twice. After spraying modification, the temperature of the intermediate spinning chamber of the continuous electrospinning machine was set to 40°C to dry it, other control parts of the spinning chamber were not started, and the winding speed was controlled to be 0.1m / min, that is, the modified PLA non-woven fabric was wound up to obtain a thickness of 0.0933mm, which was installed on the feeding reel.
[0032] (2) Using formic acid as solvent, a polyamide 6 spinning solution with a concentration of 12 wt.% was prepared, and the spinning solution was coated on the electrode wire of the electrospinning device through a pump and a mobile liquid supply device for high-voltage electrospinning. The temperature in the spinning chamber was controlled to be 60°C, the humidity was controlled to be 20%, the spinning voltage was 80 KV, the winding speed was 0.2 m / min, and the spinning time was 45 min for optimal performance. A polyamide 6 nanofiber membrane combined with a modified PLA non-woven fabric, i.e., an air filtration composite membrane material, was obtained with a thickness of 0.0966 mm.
[0033] The thickness of the sample was measured using a spiral micrometer (accuracy 0.0001mm), and the thickness of the substrate layer was measured to be 0.0930mm. The thickness of the modified substrate layer was 0.0960mm. After combining with the filter layer, the total thickness of the composite membrane material was 0.0966mm. The BET specific surface area of the material was measured using the principle of low-temperature nitrogen physical adsorption (static capacity method) using an automatic specific surface area and porosity analyzer (ASAP 2460) and was 19.7m 2 / g.
[0034] from Figure 1 It can be seen that the average diameter of the polyamide 6 fibers in the filter layer of the air filtration composite membrane material is 50 nm. Figure 2 The air filtration composite membrane material obtained in Example 1, with the spinning time, the PM of the material 0.3 The curve of filtration performance and air resistance, PM 0.3 The filtration efficiency reaches 99%.
[0035] Example 2
[0036] An air filtration composite membrane material, comprising a substrate layer and a filter layer, wherein the substrate layer is a polylactic acid nonwoven fabric modified by γ-aminopropyltriethoxysilane; the filter layer is a polyamide 6 nanofiber membrane prepared by continuous electrospinning. The thickness of the substrate layer is 0.0900 mm, the average diameter is 10 μm, the thickness of the modified substrate layer is 0.0960 mm, and after combining with the filter layer, the total thickness is 0.1020 mm, and the average diameter of the nanofibers in the filter layer is 50 nm. The porosity of the overall composite membrane material is about 75.5%, and the BET specific surface area is 20.0 m 2 / g, the substrate layer accounts for 96.3wt.%, and the filter layer accounts for 3.7wt.%.
[0037] (1) The preparation method of the above-mentioned composite membrane material for air filtration comprises the following specific steps: preparing a mixed solvent of deionized water and anhydrous ethanol in a volume ratio of 1:5, selecting a silane coupling agent γ-aminopropyltriethoxysilane, and preparing a solution with a concentration of 5 wt.%. Placing a PLA non-woven fabric roll with a width of 1 m and a thickness of 0.0900 mm on the feed roll of a continuous electrospinning machine, pouring the prepared silane coupling agent solution into a spray gun, starting the air pump to spray the PLA non-woven fabric, and controlling the spraying amount to 10 ml / cm each time. 2 , spray 10 times, after spray modification, set the temperature of the intermediate spinning chamber of the continuous electrospinning machine to 35°C, do not start other control parts of the spinning chamber, and control the winding speed to 0.2m / min, that is, the modified PLA non-woven fabric is wound up to obtain a thickness of 0.0960mm, which is installed on the feed reel.
[0038] (2) Using formic acid as solvent, a spinning solution of polyamide 6 (PA6) with a concentration of 13wt.% was prepared, and the spinning solution was coated on the electrode wire through a pump and a mobile liquid supply device. The temperature in the spinning chamber was controlled to be 60°C, the humidity was controlled to be 20%, the spinning voltage was 60KV, the spinning time was 50min, and the winding speed was controlled to be 0.5m / min, thereby obtaining a polyamide 6 nanofiber membrane combined with a modified PLA non-woven fabric, i.e., an air filtration composite membrane material with a thickness of 0.1020mm.
[0039] Figure 3 This is the SEM image of the modified PLA non-woven fabric in this embodiment. From the left image, it can be seen that the average diameter of the non-woven fabric is 10 μm; from the EDS image of the modified PLA non-woven fabric containing silicon elements (right image), it can be seen that γ-aminopropyltriethoxysilane is loaded on the fiber surface.
[0040] The porosity was calculated by the following method: the composite air filtration membrane of this embodiment was cut into a size of 2 cm × 2 cm, placed in a solvent, and completely soaked for 24 h. After being taken out, the surface liquid was quickly absorbed by filter paper, and the mass m of the wet membrane was measured. w Place the sample in a vacuum oven and dry the film to constant weight. Then measure the mass m of the dry film. d The porosity was calculated according to the following formula. Each group of samples was measured 3 times and the average value was taken to obtain the porosity of the overall composite membrane material of 75.5%.
[0041]
[0042] Where, ε is the porosity of the sample to be tested, %;
[0043] m w is the mass of the sample to be tested in wet state, g;
[0044] m dis the mass of the test sample in dry state, g;
[0045] A is the surface area of the membrane in wet state, cm 2 ;
[0046] L is the surface area of the membrane in wet state, cm;
[0047] ρ is the density of the selected solvent, g / cm 3 .
[0048] Example 3
[0049] An air filtration composite membrane material, comprising a substrate layer and a filter layer, wherein the substrate layer is a polylactic acid nonwoven fabric modified by γ-aminopropyltriethoxysilane; the filter layer is a polyamide 6 nanofiber membrane prepared by continuous electrospinning. The thickness of the substrate layer is 0.1500 mm, the average diameter is 2 μm, the thickness of the modified substrate layer is 0.1520 mm, and after combining with the filter layer, the total thickness of the composite filter membrane is 0.1600 mm, and the average diameter of the nanofibers in the filter layer is 70 nm. The porosity of the overall composite membrane material is about 90%, and the BET specific surface area is 15.0 m 2 / g, the substrate layer accounts for 95.5wt.%, and the filter layer accounts for 4.5wt.%.
[0050] The preparation method of the above-mentioned air filtration composite membrane material comprises the following specific steps:
[0051] (1) Deionized water and anhydrous ethanol in a volume ratio of 1:20 are prepared into a mixed solvent, and γ-aminopropyltriethoxysilane is selected as a silane coupling agent to prepare a solution with a concentration of 20 wt.%. A PLA non-woven fabric roll with a width of 1 m and a thickness of 0.1500 mm is placed on the feed roll of a continuous electrospinning machine, and the prepared silane coupling agent solution is poured into the spray gun, and the air pump is started to spray the PLA non-woven fabric, and the spraying amount is controlled to be 10 ml / cm each time. 2 , sprayed 3 times. After spraying modification, the temperature of the intermediate spinning chamber of the continuous electrospinning machine was set to 50°C, other control parts of the spinning chamber were not started, and the winding speed was controlled to 0.2m / min, that is, the modified PLA non-woven fabric was wound up, and the thickness of the modified substrate was 0.1520mm, which was installed on the feeding reel.
[0052] (2) Using formic acid as solvent, a spinning solution with a concentration of 12wt.% of polyamide 66 was prepared, and the spinning solution was coated on the electrode wire through a pump and a mobile liquid supply device. The temperature in the spinning chamber was controlled to be 50°C, the humidity was 30%, the spinning voltage was 80KV, the spinning time was 60min, and the winding speed was 0.2m / min. The polyamide 66 nanofiber membrane combined with the modified PLA non-woven fabric, i.e., the air filtration composite membrane material, had a thickness of 0.1600mm.
[0053] The composite air filtration membrane material prepared in this example was degraded by biological protease and ultraviolet radiation. The optical photograph of the air filtration material is shown in FIG. Figure 4 The air filtration composite membrane material prepared in this embodiment is first biodegraded by proteinase K at a concentration of 0.5 mg / ml, pH 9.0, temperature 60°C, and degradation time of 1 day, and then degraded by ultraviolet light with a wavelength of 365 nm for 3 days. Figure 4 It can be seen from the optical photographs before and after degradation that the air filter material involved in this embodiment has basically achieved complete degradation.
[0054] Obviously, the above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the invention.
Claims
1. A continuous preparation method of an air filtration composite membrane material, characterized in that: The steps include: (1) Continuous modification of nonwoven fabric substrate: A mixed solvent of water and ethanol in a volume ratio of 1:20 to 1:5 is used to prepare an amino-hydrocarbon-based silane coupling agent solution with a concentration of 1 to 20 wt.%; the degradable nonwoven fabric is placed on the feed reel of a continuous electrospinning machine and sprayed with the amino-hydrocarbon-based silane coupling agent solution at a spraying amount of 0.1 to 10 mL / cm 2 , the number of spraying times is 1 to 10 times; after the spraying is completed, the temperature is controlled at 35 to 55 ° C for drying, and the non-woven fabric substrate modified by the amino hydrocarbon-based silane coupling agent is obtained by rolling; wherein the material of the non-woven fabric is a degradable polymer material, and contains a carboxyl functional group, selected from polylactic acid, polyglycolic acid, and amino acid polymers; (2) The modified nonwoven fabric substrate obtained in step (1) is mounted on a feed reel of an electrospinning machine, and a polyamide polymer solution is used as a spinning solution for continuous spinning, the spinning chamber temperature is 20 to 60°C, the humidity is controlled at ≤50%, the nozzle is a needleless type, the spinning speed is 1 to 350 mm / s, the voltage is set at 10 to 100 kV, the spinning time is 10 to 100 min, and the winding speed is controlled at 0.1 to 2 m / min; after the continuous spinning is completed, a polyamide polymer nanofiber membrane combined with the modified nonwoven fabric substrate is obtained, namely, an air filtration composite membrane material; The BET specific surface area of the prepared air filtration composite membrane material is 0.5 ~ 20 m 2 / g, porosity 60% ~ 90%; substrate layer thickness 0.08 ~ 0.2 mm, filter layer thickness 0.001 ~ 0.010 mm, filter layer nanofiber diameter 20 ~ 500 nm; the air filtration composite membrane material for PM 2.5 The particle filtration efficiency reaches 100%, and the PM 0.3 The particle filtration efficiency reaches 99%.
2. The preparation method according to claim 1, characterized in that The polyamide polymers include polyamide 6, polyamide 610, polyamide 66, polyamide 11, polyamide 12, polyamide 1010, polyamide 56, polyamide 4, polyamide 8, polyamide 9 and polyamide 810; the amino hydrocarbon-based silane coupling agents include γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-(β-aminoethyl)aminopropyltrimethoxysilane, γ-ureapropyltriethoxysilane, anilinemethyltrimethylsilane and anilinemethyltriethylsilane.
3. The preparation method according to claim 1, characterized in that In step (2), the spinning solution polyamide polymer solution uses formic acid, acetic acid or a mixture of the two as solvent and is configured with a spinning concentration of 10 to 15 wt.%.
Citation Information
Patent Citations
Degradable bio-based air filter membrane and preparation method thereof
CN105597575A
Piezoelectric antibacterial nano-film air filter film and preparation method thereof
CN110354648A
Composite filtering material and preparation method thereof
CN110711430A
Nylon nanofiber aerogel material for air filtration and preparation method thereof
CN111116974A
Degradable nanofiber air filtering material and preparation method thereof
CN113181711A